Butterfly gardening with native plants : how to attract and identify butterflies - Kline, Christopher (Botanist) (Skyhorse Publishing, 2015)
Butterfly expert Christopher Kline provides an easy-to-read introduction and how-to guide covering butterfly gardening basics, garden designs, common butterflies in the garden, native nectar, guide to host plants, and sources for native plants. Included are over 150 color photographs as well as several detailed illustrations on garden layout. With this guide, it is easy to choose plants to attract specific species of butterflies, and Kline provides a photo guide for identifying butterflies as well. On every page there is a basic timeline to indicate the best season for both plants and butterfly sightings.